Criteria for public open space enhancement to achieve social interaction: a review paper - Abdulkareem Salih, Sarah; Ismail, Sumarni (Institute of Physics Publishing, 2018)
This paper presents a various literatures, studies, transcripts and papers aiming to provide an overview of some theories and existing research on the significance of natural environments and green open spaces to achieve social interaction and outdoor recreation. The main objective of the paper is to identify the factors that affecting social interaction in green open spaces, through proving that an appropriate open spaces is important to enhance social interaction and community. This study employs (qualitative) summarizing content analysis method which mainly focused on collect and summarizing of documentation such as transcripts, articles, papers, and books from more than 25 source, regarding the importance of public open spaces for the community. The summarizing content analysis of this paper is the fundament for a qualitative oriented procedure of text interpretation used to analyse the information gathered. Results of this study confirms that sound social interaction need an appropriate physical space including criteria of: design, activities, access and linkage, administration and maintenance, place attachment and users' characteristics, also previous studies in this area have a health perspective with measures of physical activity of open spaces in general.